A Fifteenth-Century Mamluk Astronomer in the Ottoman Realm: ‘Umar al-Dimashqī and his ‘ilm al-mīqāt corpus the Hamidiye 1453 - Taha Yasin Arslan (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
The 15th century emergence of the Ottoman scientific endeavours occurred at a fortunate time when scientific knowledge in the Islamic world was already advanced. Since the Ottomans never had an intention to reinvent the wheel, instead, they began accumulating this already advanced knowledge via several methods of transmission. Copying the manuscripts, providing safe haven for scholars who run from the political instability in the East, establishing madrasas are some among these methods. Most of the transmission of mathematical sciences such as algebra, arithmetic, ʿilm al-hayʾa etc. were from successive schools of Maragha, Tabriz, and Samarkand. The science of timekeeping, however, had a unique source: the Mamluks. The 13th-15th centuries Mamluk astronomers worked exclusively on timekeeping and produced arguably the most sufficient treatises in the area. Without a surprise, the Ottoman reception of timekeeping was based on their works. This paper will discuss the exact starting point of this transmission and introduce ʿUmar al-Dimashqī, a Mamluk astronomer from Damascus who lived in Edirne and Istanbul, as the responsible party. The texts in his timekeeping corpus, Hamidiye 1453, will be investigated in detail and this corpus will be examined for the role it played as a bridge between Mamluk, Samarqand, and Istanbul.